2010
DOI: 10.1098/rspb.2010.0392
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive gene and taxon coverage elucidates radiation patterns in moths and butterflies

Abstract: Lepidoptera (butterflies and moths) represent one of the most diverse animals groups. Yet, the phylogeny of advanced ditrysian Lepidoptera, accounting for about 99 per cent of lepidopteran species, has remained largely unresolved. We report a rigorous and comprehensive analysis of lepidopteran affinities. We performed phylogenetic analyses of 350 taxa representing nearly 90 per cent of lepidopteran families. We found Ditrysia to be a monophyletic taxon with the clade Tischerioidea þ Palaephatoidea being the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

51
387
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 304 publications
(470 citation statements)
references
References 46 publications
51
387
2
2
Order By: Relevance
“…Nature ecology & evolutioN about 104.7 Myr ago (Ma), and diverged approximately 147 Ma from the more basal Plutella xylostella, whereas Lepidoptera as a whole separated from Diptera about 258 Ma, consistent with reported divergence time estimates 10 ( Supplementary Fig. 1b).…”
Section: Articlessupporting
confidence: 83%
“…Nature ecology & evolutioN about 104.7 Myr ago (Ma), and diverged approximately 147 Ma from the more basal Plutella xylostella, whereas Lepidoptera as a whole separated from Diptera about 258 Ma, consistent with reported divergence time estimates 10 ( Supplementary Fig. 1b).…”
Section: Articlessupporting
confidence: 83%
“…Preliminary trees (not shown) supported the inclusion of Ogmograptis plus the vascular cambium-mining species within Gracillarioidea and as sister to Bucculatrix, results later confirmed by Mutanen et al (2010), who referred Tritymba to the Bucculatricidae. Bucculatrix was thus chosen as the outgroup for subsequent analyses.…”
Section: Molecular Systematicssupporting
confidence: 50%
“…In parallel to the present study, a recent phylogenetic analysis of lepidopteran relationships based on molecular evidence (Mutanen et al 2010) indicated that Ogmograptis and Tritymba are closely related and linked to Bucculatrix Zeller. This finding came as a surprise as Tritymba had been included in the Plutellidae because the antennae are held forward when the moth is at rest, unlike Ogmograptis, in which the antennae rest along the costa (Zborowski and Edwards 2007).…”
Section: Taxonomic Position Of Ogmograptismentioning
confidence: 62%
“…2), and this idea is well supported by its modal karyotype of n = 31 (refs. 17,18) and the molecular phylogeny of Lepidoptera 19,20 , indicating the importance of P. xylostella in the history of lepidopteran evolution.…”
Section: E T T E R Smentioning
confidence: 99%
“…2), and this idea is well supported by its modal karyotype of n = 31 (refs. 17,18) and the molecular phylogeny of Lepidoptera 19,20 , indicating the importance of P. xylostella in the history of lepidopteran evolution.On the basis of P. xylostella transcriptome data 11 , we identified 354 preferentially expressed genes in larvae (Supplementary Fig. 15), and a set of these genes is involved in sulfate metabolism, some of which were validated using quantitative RT-PCR for gene expression analysis (Supplementary Figs.…”
mentioning
confidence: 99%